Locating infant and early childhood mental health at the heart of social work - Walsh, Tova B. et al (Social Work: A Journal of the National of Social Workers)
Infant and early childhood mental health (IECMH)$1 (Ban interdisciplinary field dedicated to advancing understanding of early relationships, socioemotional development, and cultural and contextual influences on caregiving$1 (Boffers essential tools for social workers to support the well-being of infants, toddlers, preschoolers, and their families. Even though social worker Selma Fraiberg was a founder of the field, and social workers are central to the work of assessment and intervention with young children and their caregivers in many settings, few schools of social work offer training in IECMH, and few social workers are familiar with its core principles, scholarship, and intervention approaches. In this article, faculty members from four U.S. social work programs address the vital role of IECMH in social work training, research, and practice as well as issue a call to the field to recover and renew commitment to a practice perspective and knowledge base with roots in social work. Twenty-five years ago, Social Work published a similar call, but the request has gone largely unheeded. The authors examine the changing landscape and argue that it is more important and timelier than ever for social workers to learn and integrate the relationship-based approach to promotion, prevention, intervention, and treatment offered by IECMH.- Reproduced s
Keywords: 9